A joint model of the contractile system of striated muscle (dynamic version) - Wünsch, Z (Physiologia Bohemoslovaca, 1987)
The Joint Model of the Contractile System of Muscle is a theoretical construction and the question is whether it may express adequately some aspects of the biological original. In addition to the previous results which presented preliminary calculations, simulation experiments have been performed with a dynamic version of the model. The relations found between the variables studied (length, shortening velocity, isotonic contraction load, shortening heat production rate and excess of effective activity), did not essentially differ from those established by preliminary calculations; the choice of appropriate parameter values and the introduction of some additional features in the system made it possible to obtain a better approximation of relations known from measurements on the biological object. The model discloses some relevant general aspects of the contractile system of "independent" generators of force and thus contributes to a specification of the relationships between molecular and macroscopic levels of contraction phenomena. Future development or correction of the concepts under consideration depend on more suitable empirical data and further simulation experiments.
Keywords: Muscle Contraction; svaly; biologické modely; teoretické modely; isotonická kontrakce; biomechanika; svalová kontrakce; počítačová simulace; Biomechanical Phenomena; Muscles; Models, Biological; Isotonic Contraction; Computer Simulation; Models, Theoretical